Anti‐MDA5 positive clinically amyopathic dermatomyositis presenting with severe cardiomyopathy. (29th October 2013) - Pau‐Charles, I.; Moreno, P.J.; Ortiz‐Ibáñez, K.; Lucero, M.C.; Garcia‐Herrera, A.; Espinosa, G.; Nicolás, J.M.; Castro, P.; Grau, J.M.; Casciola‐Rosen, L.; Mascaró, J.M.
Abstract Background Anti‐MDA5 (Melanoma differentiation‐associated gene 5) positive dermatomyositis is a new variant of clinically amyopathic dermatomyositis that presents with characteristic mucocutaneous findings and is associated with a higher risk of developing rapidly progressive interstitial lung disease. Because its presentation differs from that of classical dermatomyositis, this entity can be a diagnostic challenge for the clinician. Methods & Results We present the case of a 55‐year‐old male with a 7‐month history of chill sensation, constitutional symptoms and polyarthralgia. Within 3 months, the patient developed progressive heart failure with dyspnoea and orthopnoea, together with characteristic cutaneous lesions. Skin biopsies demonstrated thrombosis of small and medium‐sized arteries in the reticular dermis, together with an evolved lobular panniculitis and prominent mucin deposits. Conclusions Clinicians should be aware of the characteristic clinical and histopathologic presentation of this variant of dermatomyositis to establish an early diagnosis. Further evidence is needed to clarify the risk of cardiac involvement in this subset of patients.